Extracorporeal shock wave promotes activation of anterior cruciate ligament remnant cells and their paracrine regulation of bone marrow stromal cells' proliferation, migration, collagen synthesis, and differentiation. Issue 8 (August 2020) - Lu, Cheng-Chang; Chou, Shih-Hsiang; Shen, Po-Chih; Chou, Pei-Hsi; Ho, Mei-Ling; Tien, Yin-Chun
Abstract : Aims: Proliferation, migration, and differentiation of anterior cruciate ligament (ACL) remnant and surrounding cells are fundamental processes for ACL reconstruction; however, the interaction between ACL remnant and surrounding cells is unclear. We hypothesized that ACL remnant cells preserve the capability to regulate the surrounding cells' activity, collagen gene expression, and tenogenic differentiation. Moreover, extracorporeal shock wave (ESW) would not only promote activity of ACL remnant cells, but also enhance their paracrine regulation of surrounding cells. Methods: Cell viability, proliferation, migration, and expression levels of Collagen-I (COL-I) A1, transforming growth factor beta (TGF-β), and vascular endothelial growth factor (VEGF) were compared between ACL remnant cells untreated and treated with ESW (0.15 mJ/mm 2, 1, 000 impulses, 4 Hz). To evaluate the subsequent effects on the surrounding cells, bone marrow stromal cells (BMSCs)' viability, proliferation, migration, and levels of Type I Collagen, Type III Collagen, and tenogenic gene ( Scx, TNC ) expression were investigated using coculture system. Results: ESW-treated ACL remnant cells presented higher cell viability, proliferation, migration, and increased expression of COL-I A1, TGF-β, and VEGF. BMSC proliferation and migration rate significantly increased after coculture with ACL remnant cells with and without ESW stimulation compared to the BMSCs alone group. Furthermore, ESW significantly enhanced ACL remnant cells' capability to upregulate the collagen gene expression and tenogenic differentiation of BMSCs, without affecting cell viability, TGF-β, and VEGF expression. Conclusion: ACL remnant cells modulated activity and differentiation of surrounding cells. The results indicated that ESW enhanced ACL remnant cells viability, proliferation, migration, and expression of collagen, TGF-β, VEGF, and paracrine regulation of BMSC proliferation, migration, collagen expression, and tenogenesis. Cite this article: Bone Joint Res 2020;9(8):457–467.